2015
DOI: 10.5539/elt.v8n6p150
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Reading and Writing: A Case Study

Abstract: Connecting reading and writing, proposed by many scholars, is realized in this case study. The 30 participants in this study are the English majors of the third year in one School of Foreign Languages in Beijing. They are encouraged to write journals every week, based on the source text materials in their Intensive Reading class, with the final piece as a reflective journal of their mind work in writing. All their journals written during the first 12 weeks of the whole semester are analyzed qualitatively. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Two of the participants in the previous study (Li, 2015) are the subjects of this research. The research lasts for 16 months (August, 2014-December, 2015.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the participants in the previous study (Li, 2015) are the subjects of this research. The research lasts for 16 months (August, 2014-December, 2015.…”
Section: Participantsmentioning
confidence: 99%
“…This model can be best used in the intensive reading class (Li, 2014). By analyzing the students' writing pieces after reading and their written introspections on their own writing processes, Li (2015) finds that journal writing helps the university students gain a better understanding of the source text, gives them a chance to review the text, cultivates their critical thinking abilities, and guarantees them a special opportunity to communicate with the teacher. Besides Reading-to-write, continuation task (writing the ending of the reading material) also proves to be an effective way (Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there have been some studies conducted dealing with reading habit and writing skill. Li (2015) in her case study revealed that reading and writing are connected to each other. The reading materials are proven to help the learners to generate ideas and information to their written work.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, this branch of scholarship seems to be continuously researched on. Among its main arguments is the interconnection between the two skills (Moran & Billen, 2014;Li, 2015;Li, 2016;Arum, 2018;Linuwih & Winardi, 2020). In fact, better authors read more than poor writers since reading functions as an invaluable resource (Al Raqqad et al, 2019) and better readers write more syntactically developed language.…”
Section: Writing In Malaysia and Its Incorporation With Reading Skillsmentioning
confidence: 99%